Initial growth of cassava plants cv. Mossoró under different water regimes - Domingos Ferreira de Mélo Neto; Daniel Gomes Coelho; Moab Torres de Andrade; Jandelson de Oliveira Alves (Agro@mbiente On-line)
The sprouting phase of cassava is critical for the establishment of the plant, with this phase being dependent on soil moisture. As such, this study evaluated the effect of different irrigation levels on the initial growth of cassava cv. Mossoró in semi-arid conditions. The experiment was conducted under completely randomized design conditions with 5 replications. The treatments in pots containing one plant per experimental unit consisted of 5 irrigation levels, 0, 25, 50, 75 and 100% of the reference evapotranspiration (ETo, mm day-1), which corresponded to totals for the experimental period of 11.20; 42.15; 73.09; 104.03 and 134.97 mm, respectively. At 30 days after planting, the number of leaves and stems, as well as the dry mass of the shoot and the root had increased sharply for irrigation levels up to 73.09 mm. For higher irrigation levels there was a tendency for plant growth stabilization; however, above 104.03 mm there was a decrease. Shoot and root dry mass ratio showed severe water stress at the 11.20 mm level, being more damaging to root growth. Plant height showed a positive linear trend as the level of irrigation was increased, as opposed to water use efficiency. Therefore, irrigation with 50% replacement of ETo (73.09 mm) provided the best conditions for early growth of cassava.